Comparison of intercanine width in between Angle class II division 1 and division 2 malocclusions - Putri, Bebby; Malik, Isnaniyah; Zenab, N R Yuliawati (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2016)
Introduction: Dental arch width measurement is needed to determine diagnoses and orthodontic treatment planning of Angle Class II Division 1 and Class II Division 2 Â malocclusions that have narrow maxillary dental arch generally. Dental arch width in this study was measured by maxillary and mandibular intercanine width. Â This study aimed to compare the differences of intercanine width between Angle Class II division 1 and Class II division 2 malocclusions. Methods: Descriptive comparative research with total samples of 67 study models, consisted of 34 Class II division 1 cases and 33 Class II division 2 cases. The minimum age of the samples chosen was 13 years old with no history of orthodontic treatment. A non probability consecutive sampling technique was used. Results: Study results showed the avarage maxillary and mandibular intercanine width of Class II Division 1 were 33,99 mm and 26,33 mm. Average maxillary and mandibular intercanine width of Class II Division 2 were 34,77 mm and 25,37 mm. Conclusions: T-test analysis showed no statistical significant differences in the intercanine width between Angle Class II Division 1 and Class II Division 2Â malocclusions.